The Effect of Provider Perception about Satisfaction of Capitation System - Sandu Siyoto (Jurnal Keperawatan, 2016)
Capitation funds distributed by BPJS to health services is providers of health care in FKTP receive regular income per participant, per period of time for which the service has been determined. From the initial survey results were done, there are some respondents who are not satisfied with the capitation system. The purpose of this study was to investigate the effect of provider perception about satisfaction of capitation system.The design study is a quantitative research using a "cross sectional". The sampling technique used Total Sampilng by sample as much 35 providers. Data analysis technique using linear regression. The results showed that 17.6% provider had an excellent perception about capitation system and 82.4% had agood enoughperception, as many as 70.6% provider were satisfied and 29.4% were not satisfied with capitation system. Results of analysis using linear regersi showed that p-value = 0.000 <α = 0.05, so H0 is rejected, meaning that perception significantly affect satisfaction. Provider satisfaction in this case is Health Facilities of First Level need to be considered because it will impact provision of services to patients, which indirectly will give satisfaction to patients BPJS with services provided by doctors, dentists and clinics or to system on the Agency Organizer Social Security Health in Kediri City